2020
DOI: 10.1186/s42155-020-00117-2
|View full text |Cite
|
Sign up to set email alerts
|

Single institutional experience of peripheral applications of a liquid embolic agent: Ethylene Vinyl Alcohol Copolymer

Abstract: Objective To evaluate the safety and efficacy of ethylene vinyl alcohol (EVOH) copolymer for the treatment of a variety of peripheral vascular pathologies. Results Between October 2010 and October 2017, 43 patients who underwent total 54 EVOH embolization procedures for the treatment of peripheral vascular pathologies were included. The cases which involved the use of EVOH for the treatment of nonvascular, neurologic, ophthalmologic, otolaryngologic or head-neck patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…77 The use of n-BCA alone as an embolic is limited owing to the lack of control when delivering it and steep learning curve for operator use. 78 It is commonly used for thrombosis of large aneurysms or when coiling is insufficient to cause blood stasis. However, there has been an increase in the use of n-BCA for managing LGIB.…”
Section: Embolic Agentsmentioning
confidence: 99%
“…77 The use of n-BCA alone as an embolic is limited owing to the lack of control when delivering it and steep learning curve for operator use. 78 It is commonly used for thrombosis of large aneurysms or when coiling is insufficient to cause blood stasis. However, there has been an increase in the use of n-BCA for managing LGIB.…”
Section: Embolic Agentsmentioning
confidence: 99%
“…6 Combined utilization of sclerotherapy and embolotherapy techniques during treatment of peripheral vascular malformations has the potential to achieve zero occurrences of non-target embolization in experienced operators' hands. 7,8 Nevertheless, no sclerosing agent is immune to the potential risk of non-target embolization, especially in the setting of larger caliber draining veins. 9 Balloon occlusion offers a means of temporarily blocking these connections to the systemic circulation to allow for more complete sclerotherapy in addition to reducing the risk of non-target venous occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…1 In a single center review, Onyx had an 89% clinical success rate in a variety of conditions, including aortic stent graft endoleaks, peripheral AVMs, and hemorrhage. 2 Mahdjoub et al reported 100% efficacy in treating renal hemorrhage in 24 patients. 3 Mozes et al reported successful treatment of type II endoleaks in aortic stent grafts in 72% of patients.…”
mentioning
confidence: 99%